2021
DOI: 10.3390/ijerph18168548
|View full text |Cite
|
Sign up to set email alerts
|

Protective Factors That Foster Resilience to HIV/AIDS: Insights and Lived Experiences of Older Gay, Bisexual, and Other Men Who Have Sex with Men

Abstract: Since the beginning of the HIV/AIDS epidemic, gay, bisexual, and other men who have sex with men (gbMSM) have been disproportionately impacted by HIV/AIDS health disparities. Research showed that resilience to HIV/AIDS is associated with increased use of relevant health services, lower sexual health risks, and improved mental health outcomes among racially and ethnically diverse gbMSM. As the subpopulation that has historically been impacted by HIV/AIDS the longest, older gbMSM living with HIV/AIDS have inargu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…Resilience development was also fostered through access to others’ lived experience (e.g., through HIV centers and support groups), which helped men re-assess their own internal responses to both internalized and external stigmas and provided suggested coping strategies (e.g., mindfulness, advice on sexual orientation or HIV disclosure, and dating with HIV). The current findings reflect Canadian studies (Liboro et al, 2021a, b ) that found access to HIV information and support services fostered internal and external resilience and are important factors in HIV health management. Sadly, access to such services is not fully equitable throughout Australia and participants in this study moved to the city for such services.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Resilience development was also fostered through access to others’ lived experience (e.g., through HIV centers and support groups), which helped men re-assess their own internal responses to both internalized and external stigmas and provided suggested coping strategies (e.g., mindfulness, advice on sexual orientation or HIV disclosure, and dating with HIV). The current findings reflect Canadian studies (Liboro et al, 2021a, b ) that found access to HIV information and support services fostered internal and external resilience and are important factors in HIV health management. Sadly, access to such services is not fully equitable throughout Australia and participants in this study moved to the city for such services.…”
Section: Discussionsupporting
confidence: 85%
“…Much international HIV stigma research over the past decade has sought to quantify resilience through scores on self-report scales that measure the individual, interpersonal, or community-level resources that individuals might utilize to strengthen resilience (Brewer et al, 2020 ; Dulin et al, 2018 ; Gottert et al, 2019 ; Hussen et al, 2017 ). While these studies demonstrate that individuals who have access to such resources report higher resilience scores, these quantitative measures do not capture the multifaceted construct of stigma experience (e.g., multiple adversities or access to HIV-support services or LGBTQIA+ inclusive providers) that impacts on resilience development as evident in qualitative research findings (Dulin et al, 2018 ; Emlet et al, 2011 ; Harper et al, 2014 ; Liboro et al, 2021a , b ). Thus, the need to understand these complex processes invites research on the multifaceted nature of stigma, for example, via applying intersectionality theory (Cole, 2009 ) to stigma research.…”
Section: Introductionmentioning
confidence: 95%
“…The majority of previous research conducted on resilience to HIV/AIDS in the past decade has historically utilized quantitative studies that employed frameworks, surveys, scales, and general measures to approximate the concept of resilience to HIV/AIDS, which were neither customized for the context nor established with the perspectives and direct input of PLWH (Dulin et al, 2018;Emlet et al 2013;Gottert et al, 2019). Notably, several research studies on resilience to HIV/AIDS that were conducted in the last 10 years have not exclusively focused on factors nor generated findings specific to individual attributes that PLWH possessed or mustered, but instead have examined and documented the importance of external factors to forging resilience to HIV/AIDS such as social support from family and friends, improved access to HIV treatment and care, and increased use of health services in the community (Emlet et al, 2013;Green & Wheeler, 2019;Harper et al, 2014;Harrison & Li, 2018;Liboro et al, 2021;Owens et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that can affect homosexual resilience (gay) is a psychosocial factor that is owned so that it can affect homosexual resilience one of which is gay (Lyons et al, 2016). In Liboro et al (2021) revealed that factors that can protect homosexual resilience (gay) are stable protection factors including spirituality, social support from friends and the environment, as well as educational factors, then the habit or behavioral factors that include activeness in participating in volunteer activities. The thing described above proves that resilience in homosexuals (gay) is not related to parenting style.…”
Section: Hypothesis Testmentioning
confidence: 99%